Mobile application validation for Peritoneal Dialysis patients and caregivers (Research, Society and Development, 2022)
The study aimed to validate the content and form of a prototype application for mobile devices, in order to support the self-care actions of patients on peritoneal dialysis at home and/or their caregivers. It is a methodological study with a quantitative approach developed in the following stages: integrative literature review, production of an application prototype validation instrument and content validation by expert judges. Data for content validation were collected through a self-completion questionnaire prepared in Google Forms and sent by email. The degree of agreement was verified through the Content Validation Index. Questions 01 and 05 received CVI = 0.83. Questions 02, 03, 04, 06, 07 and 08 received CVI = 1.0, reaching a desirable score, higher than 0.90. The prototype application for mobile devices for patients on peritoneal dialysis and caregivers proved to be valid in terms of content and form, with the potential to assist patients in the process of peritoneal and/or family dialysis, mediated by nephrologist nurses.